Success of the PCR-based replication assay depends on the number of methylation sensitive restriction sites in the PCR amplifying region - Metta, M K; Tantravahi, S; Kunaparaju, R (Cellular and Molecular Biology, 2015)
The PCR-based replication assay is one of the most simple, quick and economical methods for the analysis of episomal replication. However, in spite of its advantages the method has not been able to replace the southern-based replication assay, the latter of which is a tedious and time-consuming process. This is due to the generation of spurious amplification products in the PCR-based replication assay. The replication assay is based on the use of methylation-sensitive restriction endonucleases (eg. DpnI, MboI) to distinguish bacterial replicated (adenosine methylated) and mammalian replicated plasmids (adenosine non-methylated). In this work we addressed the problem by evaluating (a) restriction enzyme digestion and (b) the minimum number of restriction sites that are required in the amplifying region. The efficiency of restriction digestion was tested by subjecting the plasmid to one and two rounds of digestion. Multiple rounds of digestions were found to be inefficient in preventing false positives when the number of DpnI sites in the amplifying region is less than 8. However, use of a minimum of 15 DpnI sites in the amplifying region was found to overcome the false positives.